Narraciones andinas coloniales. Oralidad y visualidad en los Andes - José Luis Martínez C.; Paula Martínez S. (Journal de la Société des Américanistes)
During the colonial period (16th-18th centuries), various visual and oral texts, produced or registered by Andean people, continued to circulate. Among them, stand out the queros or wooden cups used for drinking chicha in ritual contexts of reciprocity, and the fragments of oral texts collected in works like that of Huarochirí or those of Guaman Poma de Ayala and Pachacuti Yamqui. This paper argues that there was a close connection between the semiotics of oral and written narratives and those that can be identified in the scenes that decorated the colonial queros. This provides a better understanding of the visual and oral Andean language of that period, expanding the corpus of sources that can be used to achieve a better knowledge of the Andean voices of that period.